Methyl functionalization on conjugated side chains for polymer solar cells processed from non-chlorinated solvents. Issue 33 (22nd July 2020) - Zhang, Chun-Hui; Lin, Fengyuan; Huang, Wei; Xin, Jingming; Wang, Jiang; Lin, Zhichao; Ma, Wei; Yang, Tingbin; Xia, Jiangbin; Liang, Yongye
Abstract : Methyl functionalization on conjugated thiophene side chains is developed as an effective fine-tuning approach for polymeric donors, affording substantial efficiency improvement for polymer solar cells processed from non-chlorinated solvents. Abstract : Structure fine-tuning is effective to optimize the energy level matching and morphology in polymer solar cells (PSCs), and is important to enhance the photovoltaic performance. Here, we report a fine-tuning approach by introducing a methyl group in the 4-position of the conjugated thiophene side chains. A series of polymeric donors are synthesized based on benzo[1, 2- b :4, 5- b ′]dithiophene (BDT) units with 4-alkyl-5-(2-ethylhexyl)thiophene conjugated side chains. Methyl, ethyl, and n -hexyl are employed as the 4-alkyl groups to afford polymers PMT49, PET52, and PHT53, respectively, and PTh37 is the control polymer without 4-alkyl groups. It is found that the introduction of a 4-alkyl group can lower the energy levels, leading to enhanced open-circuit voltage ( V OC ) of PSCs. PMT49 shows higher charge mobilities in blend films and more optimized morphology with smaller domain size and little decrease of domain purity than other alkyl group modified polymers. As a result, PMT49:ITIC PSCs processed from toluene exhibit a better average power conversion efficiency (PCE) of 12.0% than the PTh37 (10.6%), PET52 (9.68%) and PHT53 (7.85%) based PSCs. Furthermore, PMT50 with the 5-(2-ethylhexylthio)-4-methylthiophene side chains is synthesized. PMT50:Y6(BO) PSCs exhibit an impressive average PCE of 15.1% when processed from 1, 2, 4-trimethylbenzene, significantly higher than the devices processed from PEHTT:Y6(BO) without methyl functionalization (12.8%). Our studies suggest that methyl functionalization on conjugated side chains is a simple but effective fine-tuning strategy to develop conjugated polymers for high performance PSCs processed from non-chlorinated solvents.